Empty Box in Regional Elections: Democratic Legitimacy and Institutional Imbalance in Government - Yandy, Eza Tri; Faishal Taufiqurrahman; Devi Andani (As-Siyasi: Journal of Constitutional Law, 2025)
This study examines the emergence of the empty box phenomenon in regional elections in Indonesia and its implications for democratic principles and institutional balance. Following Constitutional Court Decision No. 100/PUU-XIII/2015, the trend of empty box candidacies has consistently increased from the 2015 to 2024 elections. Employing a normative juridical approach, this paper analyzes statutory regulations and Constitutional Court rulings to assess the democratic legitimacy and institutional equilibrium affected by uncontested elections represented by the empty box phenomenon. The findings of this study conclude that the empty box serves as a control mechanism to uphold democratic principles, fostering the development of an inclusive and competitive democracy. However, this phenomenon also poses risks of weakening governmental institutions, such as diminishing legislative oversight over the executive, increasing the potential for abuse of power, undermining governmental legitimacy, and giving rise to the threat of autocratic legalism. In addition, the victory of the empty box in regional elections leads to the necessity of conducting re-election, which ultimately imposes a financial burden on regional budgets. Ideally, such budget allocations should support regional development programs and public service delivery